2019
DOI: 10.1016/j.jshs.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the physical environment and park-based physical activity: A systematic review

Abstract: HighlightsPaths/trails and lighting received convincing support in promoting park-based physical activity.The association between incivilities and park-based physical activity was consistently positive.Seven park environment characteristics were mixed in relation to park-based physical activity.The density of and proximity to parks represented inconsistent evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 58 publications
(126 reference statements)
6
91
0
4
Order By: Relevance
“…Similarly, Smith et al systematically reviewed 28 studies from the US and Australia, and reported significant positive relationships between destination accessibility, travel and total PA [1]. A recent systematic review of 25 studies by Zhang et al [16] investigated the impact of BE characteristics in parks in North America, Australia, and Europe, and reported significant positive associations between park-based leisure PA, park lighting and walking and cycling trails. However, these findings may not generalize to LMIC contexts, where BE attributes are distinct from developed countries with respect to patterns of land-use, density, design and urbanization [17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Smith et al systematically reviewed 28 studies from the US and Australia, and reported significant positive relationships between destination accessibility, travel and total PA [1]. A recent systematic review of 25 studies by Zhang et al [16] investigated the impact of BE characteristics in parks in North America, Australia, and Europe, and reported significant positive associations between park-based leisure PA, park lighting and walking and cycling trails. However, these findings may not generalize to LMIC contexts, where BE attributes are distinct from developed countries with respect to patterns of land-use, density, design and urbanization [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is also plausible that other environmental and social variables were more salient determinants of students' physical activity behavior in the present study than the psychological determinants identi ed in the current model. Research based on ecological determinants [73,74] and socio-structural predictors [75,76] of physical activity behavior illustrate the myriad of potential determinants of children's leisure-time physical activity engagement, and a focus on psychological determinants alone may have neglected other potential predictors. As an example, students' activity levels may have been in uenced by environmental factors, such as access to sport clubs, ability to walk to school, and taking part in organized physical activity in their leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects concern for example the design and use of the transport infrastructure [17] such as walkways, railings and rest stops. Other studies of PBPA, but not with respect to the elderly, revealed that perceived cleanliness in parks was negatively related to PA [18]. Ries et al [19] and Lackey et al [20] also posited that perceived access to parks was associated with PBPA.…”
Section: Introductionmentioning
confidence: 96%
“…Ries et al [19] and Lackey et al [20] also posited that perceived access to parks was associated with PBPA. Although associations between physical environments and psychosocial factors are supported for recreational walking [21,22], active transport [15], and overall PA [15,22] of older adults, the relationships have not been systematically investigated in the context of PBPA, let alone for PA of the elderly and intercultural comparison [18]. Based on the results of various systematic reviews of PA correlates in older adults [22,23], studies are needed to assess the association between specific environmental and personal characteristics with older adults' active park use.…”
Section: Introductionmentioning
confidence: 99%